Histone Modifications and Chondrocyte Fate: Regulation and Therapeutic Implications - Wan, Chao; Zhang, Fengjie; Yao, Hanyu; Li, Haitao; Tuan, Rocky S. (Frontiers in Cell and Developmental Biology, 2021)
The involvement of histone modifications in cartilage development, pathology and regeneration is becoming increasingly evident. Candidate molecules or drugs that target histone modifying proteins have shown promising therapeutic potential in the regulation of chondrocyte biology or the treatment of cartilage lesions associated with joint degeneration, injury, and other chondropathies. Understanding the molecular mechanisms and consequences of histone modifications in cartilage development, homeostasis and pathology is of great importance, as it provides a fundamental and precise perspective to interpret biological behavior of chondrocytes and to develop novel therapies for cartilage repair or regeneration. In this review, we have summarized advances in the understanding of histone modifications in the regulation of chondrocyte fate, and cartilage development and pathology, particularly the molecular writers, erasers and readers involved. In addition, we have also covered recent studies on the use of small molecules and drugs to manipulate histone signals associated with chondrocyte functions or cartilage lesions, and their potential therapeutic benefits and limitations for preventing degeneration or promoting regeneration of articular cartilage.